Proposição de um roadmap para a implantação da abordagem do pensamento sistêmico em organizações - Corcini Neto, Secundino Luis Henrique (Universidade do Vale do Rio dos Sinos, 2010)
This research appears in the form of a roadmap, a guide for organizations that want to move towards the implementation of the Systems Thinking approach in its management. This work has been based on three pillars: i) theoretical study of a nationally and internationally on the topict, ii) completion of a case study in the company Samarco S/A, which has ten years experience with Systems Thinking and iii ) contributions from a specialist with experience in publications and application of the systemic method. The fruit of this research materializes in the form of a roadmap, which are the main points to consider in the process of implementation of systems thinking as an approach associated with management. The structure of the roadmap consists of a set of steps divided into three main processes: preparing, communicating and operationalizing. Also presented are the main critical success factors and failures that may enhance or mitigate the success of this deployment. This study focuses on the deployment of systems thinking through a roadmap and not applying the same through a systemic approach.
Keywords: Pensamento sistêmico; Roadmap; Systems thinking; ACCNPQ::Engenharias::Engenharia de Produção